PENDUGAAN NILAI EKONOMI POHON DALAM MENGHEMAT ENERGI LISTRIK PADA PERUMAHAN - Noril Milantara; Bambang Sulistyantara; Aris Munandar (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Residential areas tend to have warmer temperatures than the vegetated areas. Trees around the building are able to cool down the ambient temperature, reduce the electric demand from air conditioning use, and help reduce the emissions of fossil fuel power plants in the atmosphere. The purpose of this study was to calculate the economic value of trees benefits in electrical energy use within residential area, to analyze the value of carbon storage in trees, and to predict the ten-year economic benefit. The research was conducted using spatial approach through CITYgreen®.The result showed that classical residential has 8,5% trees canopy over 39,25 Ha of total analysis. The total economic value gained in one area was 43.6 million rupiah, or Rp.76,918/house (2.3%). New residential has 6% canopy over 71.97 Ha, and provide total savings of 90 million rupiah, or Rp.29,571/house (0.88%). Predictions for the next ten years showed the expansion of the canopy. Canopy in classicl residential expanded to 8.67% but the economic benefits were reduced to 36 million rupiah or Rp.63,610/house (1.9%). Meanwhile, canopy in new residential reach 7% with the benefits gained increased to 106 million rupiah, or Rp.35,076/house (1.05%). The economic benefits provided by trees are depended on its distance, location, and the size of the canopy. Keywords: landscape analysis, residential landscape, energy conservation, economic value, CITYgreen®